Pengaruh Pemberian Pakan Berbeda Pada Laju Pertumbuhan Ikan Lele Dumbo (Clarias gariepinus) - Mahendra, I Putu Eka; Arthana, I Wayan; Dewi, Ayu Putu Wiweka Krisna (Bumi Lestari, 2022)
Aquaculture is one of the efforts made to increase fishery production at present and in the future. One type of freshwater aquaculture that is a leading commodity and is widely cultivated by the community is catfish. Different feeding effect on the growth of African catfish fry. This study used 3 different treatments, A feeding 100% silk worms, B feeding 100% maggot and the last C feeding 50% silk worms and 50% maggot.This study aims to determine the specific growth rate, feed conversion ratio (FCR) and Survival rate (SR) in catfish fry fed different feeds of silk worms and BSF maggots Based on the results of research for 30 days from March 2021 - April 2021, the specific growth rate got the highest results, namely in treatment A, namely feeding 100% silk worms and the lowest was in feeding treatment with 100% maggot BSF. According to the treatment given, the results of the growth rate obtained were treatment A of 4.52%, treatment B of 4.13%, treatment C of 4.39%. The lowest FCR results were found in the feeding of 100% silk worms and the highest in the treatment of feeding 100%. The results of the Feeding Conversion Ratio (FCR) or the feed conversion ratio obtained were treatment A which was 1.12, treatment B was 1.68, treatment C of 1.18. In the SR parameter, the highest results were obtained in treatment A, namely feeding 100% silk worms and the lowest in treatment B, namely feeding 100% maggot BSF. The results of the survival rate in this study were 79% in treatment A, treatment B 75%, treatment C 70%.